Could 137Cs remediation be accomplished with stable cesium (CsCl) on tropical soils? - Donha, Riviane Maria Albuquerque [UNESP]; Roque, Mário; Boaretto, Antônio Enedi; Ferraudo, Antonio Sergio [UNESP]; Santos, Elcio Ferreira; Macedo, Fernando Giovannetti [UNESP]; Melo, Wanderley José [UNESP]; Junior, José Lavres (Southern Cross Publishing, 2019)
Stable cesium can be considered as the best element for desorption of soil radio-cesium. It is considered an element that slightly absorbed by plants, so that the application of high doses to the soil could increase the absorption of 137Cs, which is desired for the remediation of contaminated soils. There is shortage of knowledge on remediation of tropical and subtropical soils contaminated with 137Cs. The aim of this work was to evaluate the use of 133Cs for the remediation of Brazilian tropical and subtropical soils contaminated with 137Cs. In addition, we investigated the Cs uptake by bean plants (Phaseolus vulgaris L.) grown in Cs contaminated soil. The experiment was carried out in pots under greenhouse conditions. Seven soil types were used in the experiment (Oxisol, Udox, Psamment, Ochrept; Aquoll; Udox and Udult), which received the application of four doses of 133Cs (0, 5, 10 and 20 mg/pot in a completely randomized design arranged in a factorial scheme (7 soil types x 4 doses of 133Cs) with three replicates. An increase in transfer factor values of 137Cs was observed for both shoot growth and grains, as well as in percentage of total activity of 137Cs removed from the soil regarding to addition of stable cesium levels in all soils. The results showed that psamment soil presented higher specific activity of 137Cs in the soil and grains, as well as for the transfer coefficient from soil to shoot growth and grains. The application of stable cesium chloride to soil did not cause any effects on dry matter production of shoot growth and grains. The addition of 133Cs increased the transfer from soil 137Cs to the plant regardless of soil type, proving the efficiency of this practice for the remediation of soils contaminated with radioactive Cs. In addition, the plants of common bean were efficient for use in phytoremediation.
Keywords: Environmental pollution; Heavy metals; Phaseolus vulgaris; Phytoremediation; Transfer factor